Self-Assembly Iron Oxide Nanoclusters for Photothermal-Mediated Synergistic Chemo/Chemodynamic Therapy - Xiang Li; Zhen Wang; Mian Ma; Zhouqing Chen; Xiang-long Tang; Zhong Wang (Journal of Immunology Research)
Background and Purpose. Although chemodynamic therapy (CDT) is promising for cancer treatment, its clinical application is still limited because of unresolved issues. In this study, an efficient CDT agent for synergistic chemo/CDT therapy mediated by the photothermal effect was developed by an iron oxide self-assembly method. Methods. Superparamagnetic iron oxide nanoclusters (SPIOCs) were located within the core, which resulted in high photothermal conversion and outstanding generation of reactive oxygen species (ROS). The shell consisted of a human serum albumin- (HSA-) paclitaxel (PTX) layer, which extended the blood circulation time and ensured the effectiveness of the chemotherapy. Arg-Gly-Asp peptides (RGD) were linked to the naked cysteine moieties in HSA to promote the specific targeting of human glioma U87 cells by αvβ3 integrins. Continuous near-infrared light irradiation triggered and promoted the synergistic chemo/CDT therapy through the photothermal effect. Results. Our SPIOCs@HSA-RGD nanoplatform showed well biocompatibility and could target glioma specifically. Photothermal conversion and ROS burst were detected after continuous 808 nm light irradiation, and a significant antitumor effect was achieved. Conclusion. Experimental in vitro and in vivo evaluations showed that our photothermal-mediated chemo/CDT therapy could efficiently inhibit tumor growth and is therefore promising for cancer therapy.